Maternal-Fetal Medicine Subspecialists' Provision of Second-Trimester Termination Services - Kerns, Jennifer L.; Steinauer, Jody E.; Rosenstein, Melissa G.; Turk, Jema K.; Caughey, Aaron B.; D'Alton, Mary (American Journal of Perinatology, 2012)
Objective Most abortions for pregnancy complications occur in the second trimester. Little is known about whether maternal-fetal medicine subspecialists (MFMs) perform terminations for these women.Study Design We surveyed all members of Society of Maternal Fetal Medicine by e-mail or mail regarding second-trimester abortion provision. We conducted analyses of whether MFMs perform abortions, by what method, and how frequently.Results Our response rate was 32.4% (689/2,125). Over two-thirds of respondents perform either dilation and evacuation (D&E) or induction; 31% perform D&Es. Male gender, frequent chorionic villus sampling provision, and being trained in D&E during fellowship are associated with performing D&Es. Nonprovision of any second-trimester abortion is significantly associated with age over 50, nonacademic practice setting, and less supportive abortion attitudes (p < 0.001). A nonsignificant trend toward association between south/southeast region and nonprovision of any second-trimester abortion is seen (p = 0.09).Conclusion Many MFMs include D&E and induction termination services in their practice. Supporting current D&E providers and expanding training options for MFMs may optimize care for women diagnosed with serious pregnancy complications.
Keywords: fetal anomalies; fetal demise; pregnancy complications; termination of pregnancy